The Pragmatics Model of Bhur'maen “Beggar” Madura in Social Construction Perspective - Fajar Surahman; Ishomuddin Ishomuddin; Tri Sulistyaningsih; Rinikso Kartono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Bhur'maen is a social entity in Madurese terminology that is pinned on certain people or forms of society that are accustomed to begging for daily activities in the form of harvests or money whose modus operandi is to visit people's homes. This study aims to understand by describing the phenomenon of social problems in the context of the habits of the bhur’maens in Madura which have been carried on for generations (regeneration), thereby popping the pragmatic model of the bhur’maen community in the perspective of social construction. The analytical approach used is a qualitative approach. In the interest of this research the research paradigm rests on the paradigm of social definition by using the dialectical model of Peter L. Berger and Thomas Luckmann's Social Construction as a theoretical foundation for a sociological perspective, which focuses on the social construction of society towards the reality of bhurmaens in the Tlanakan area of Pamekasan Madura which is stigmatized as a sub-district of bhurmaen . Data collection is done by observation, interview, documentation and focus group discussion (FGD) techniques. The results and in-depth discussion in the research show: First, that the socio-cultural construction of bhur'maen is formed based on the knowledge and experiences of individuals and or actors in understanding the reality of bhur'maens in Madura. Secondly, that the bhur’maen socio-cultural construction is formed based on the values that are held by individuals and or actors in understanding the reality of bhur’maens in Madura. Third, that the socio-cultural construction of bhur'maen is formed based on the recognition (legitimacy), beliefs and beliefs of individuals and / or actors in understanding the reality of bhur’maen in Madura.